A meta-heuristic algorithm based on Henry's law for the load-following of a two-point PWR model. (January 2023) - Mousakazemi, Seyed Mohammad Hossein
Abstract: Henry's law has become the basis of a new meta-heuristic algorithm called Henry gas solubility optimization (HGSO). The novelty of this research is based on the use of this new algorithm in an important issue in nuclear energy, that is, reactor dynamics. The results can signify the validity of HGSO optimization process by comparing with established methods such as particle swarm optimization along with many studies conducted in different sciences. The two-point model of a pressurized light-water nuclear reactor (PWR) is controlled by an HGSO-tuned PID controller based on the integral of the time-weighted absolute error performance index and the axial offset following strategy. A Lyapunov approach guarantees the stability of the tuned PID. Unlike conventional theoretical estimating methods, these algorithms require the least mathematical calculations with the highest accuracy and speed to achieve optimal responses. The results signify the efficiency of this method than an empirically tuned PID, with the least mathematical calculations.